Risk factors for obstructive complications after endoscopic correction of vesico-ureteral reflux using polyacrylate polyalcohol copolymer. Issue 22 (29th May 2020) - Sizonov, Vladimir V.; Kagantsov, Ilya M.; Mayr, Johannes M.; Akramov, Nail R.; Pirogov, Aleksandr V.; Gasanov, Zhalil A.
Abstract : Abstract: Use of polyacrylate-polyalcohol copolymer (PPC) after endoscopic correction (EC) of vesico-ureteral reflux (VUR) is highly effective but is associated with a higher risk of obstructive complications (OC) compared with other implants. We undertook a STROBE compliant retrospective investigation and studied the OC risk factors to increase the practical safety of PPC. Overall, 798 patients (464 [58.1%] girls and 334 [41.9%]) boys) from 5 hospitals in whom PPC was routinely used were evaluated retrospectively. The patients were subdivided into 2 groups. Group I consisted of 754 (94.5%) children (449 [59.5%] girls and 305 [40.5%] boys) without OC. Median age was 41 months [Q1: 18.0; Q3: 81.0]. Group II comprised 44 (5.5%) patients (29 [65.9%] boys and 15 [34.1%] girls) experiencing OC, and their median age was 21.5 months [Q1: 12.0; Q3: 43.0]. Clinical and renal ultrasound examinations were carried out 1 day and 1 month after EC, and then every 6 months after EC. At the follow-up examination approximately 6 months after EC, voiding cysto-urethrography (VCUG) was performed. All patients with OC underwent diuretic renography. OC occurred in 44 (5.5%) of 798 children, in some cases as late as 60 months after endoscopic injection of the bulking agent PPC for correction of VUR. Univariate analysis revealed that younger age ( P  < .001), higher grade of VUR ( P  < .001), male gender ( P  < .001), second injection ( P  = .003), and EC injection using hydrodistension implantation technique (HIT; P  < .001) represented significant risk factors. At multivariate analysis, only male gender ( P  = .0078), younger age ( P  = .0044), HIT technique ( P  < .0001), and second injection ( P  = .04) represented significant risk factors for the occurrence of OC. We identified young age, male gender, high reflux grade, HIT technique, and second endoscopic injections as factors associated with the risk of OC after EC of VUR using PPC as a bulking agent. Thus, patients who have undergone EC with PPC must be monitored sonographically for occurrence of OC for at least 60 months after the intervention.